Mock Spanish? No Problemo - Snyder, Kristen (My University, 2011)
"Mock Spanish," a term coined by anthropologist and linguist Jane Hill, describes the incorporation of grossly non-standard and ungrammatical utterances into an English discourse. This study seeks to find out what context and by whom Mock Spanish is used, what it is the speaker intends to convey, and what is understood by the hearer when it is used.
Color poster with text, images, and charts.
Keywords: Mock Spanish; Spanish language--Influence on English; English language--United States--Foreign words and phrases--Spanish; Spanish language--Errors of usage; Posters